APPLICATION OF Ananas comosus (L.) Merr. EXTRACT WITH LOCAL MICROORGANISMS FORMULATION Solanum lycopersicum (L.) AND Saccharum officinarum Linn. BAGASSE IN ORGANOSOL SOIL MEDIUM ON THE GROWTH OF Brassica oleracea (L.) Alboglabra Group PLANTS - Erwin Junaidi Lubis; Sartika Pakpahan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Organosol soil has a very high content, but has a low soil acidity (pH) (acidic). As well as the occurrence of very slow decomposition of organic matter. The treatment with Ananas comosus (L.) Merr. extract, which contains bioactive compounds such as bromelain enzymes, organic acids, and simple sugars, can accelerate the decomposition of organic matter and support the activity of soil microorganisms. The Local Microorganisms (MoL) applied, such as Solanum lycopersicum (L.) and Saccharum officinarum Linn., contain various functional microbes such as Lactobacillus sp., Saccharomyces sp., and Azotobacter sp., which play a role in nitrogen fixation, phosphate solubilisation, and organic matter decomposition. Overall, the results of research and observations conducted on Organosol soil media treated with Ananas comosus (L.) Merr. extract with the addition of Local Microorganisms (MoL) Solanum lycopersicum (L.) and Saccharum officinarum Linn. has been proven to effectively improve the chemical properties and fertility of Organosol soil through its role in increasing microbial activity and accelerating the decomposition of organic matter. This indicates that innovations in the application of fruit and the role of local microorganisms have the potential to be developed as environmentally friendly technologies for sustainable soil management.